2020
DOI: 10.1186/s12882-020-01831-8
|View full text |Cite
|
Sign up to set email alerts
|

Gait speed and handgrip strength as predictors of all-cause mortality and cardiovascular events in hemodialysis patients

Abstract: Background Low physical performance in patients undergoing maintenance hemodialysis is associated with a high mortality rate. We investigated the clinical relevance of gait speed and handgrip strength, the two most commonly used methods of assessing physical performance. Methods We obtained data regarding gait speed and handgrip strength from 277 hemodialysis patients and evaluated their relationships with baseline parameters, mental health, plasma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 58 publications
4
27
1
Order By: Relevance
“…It implied that the muscle function of the lower extremities may be important in cardiovascular outcomes. Consistent with our findings, recent studies revealed gait speed was associated with an increased HRs for death and cardiovascular mortality (44,45).…”
Section: Discussionsupporting
confidence: 93%
“…It implied that the muscle function of the lower extremities may be important in cardiovascular outcomes. Consistent with our findings, recent studies revealed gait speed was associated with an increased HRs for death and cardiovascular mortality (44,45).…”
Section: Discussionsupporting
confidence: 93%
“…Whilst the concept of probable sarcopenia is new, the recognition of low muscle strength as a prognostic marker is well established 39,40 . HGS is shown to be a reliable nutritional marker in dialysis patients 41 and low HGS predicts mortality in patients with ESRD 42–44 . We found that CKD and non‐CKD participants with probable sarcopenia had a 33% and 37% greater risk of death.…”
Section: Discussionmentioning
confidence: 77%
“…It was interesting to note that within the sarcopenia and malnutrition group, the mean values of body fat markers, such as BMI, percentage of body fat, and standard triceps SKFs were within the normal range for non-CKD individuals (15,30,31). Similarly, Lee et al (32) also observed in a group of older adults on HD that patients with low gait speed and low HGS combined had BMI within the normal range. Additionally, in the study from Ren et al (24), no significant differences were found between no-sarcopenia and sarcopenia in relation to anthropometric indexes, namely TSF, BMI, MAC, and MAMC.…”
Section: Discussionmentioning
confidence: 84%
“…As far as we are concerned, there are no previous studies assessing the role of malnutrition and sarcopenia combined in older adults on HD, but studies in older adults hospitalized without CKD, showed that older adults with combined sarcopenia and malnutrition had a risk for mortality of close to five times higher when compared to the group with none of these nutritional disturbances (38). In patients on dialysis, previous studies have consistently shown that malnutrition (36,39), sarcopenia (25), and low muscle strength (23,32,40) were associated with increased mortality. Some limitations and strengths of this study can be listed.…”
Section: Discussionmentioning
confidence: 96%